Prenatal Diagnosis and Genetic Analysis of 21q21.1–q21.2 Aberrations in Seven Chinese Pedigrees - Hu, Huamei; Zhang, Rong; Ma, Yongyi; Luo, Yanmei; Pan, Yan; Xu, Juchun; Jiang, Lupin; Wang, Dan (Frontiers in Genetics, 2021)
Background: Chromosomal aberrations contribute to human phenotypic diversity and disease susceptibility, but it is difficult to assess their pathogenic effects in the clinic. Therefore, it is of great value to report new cases of chromosomal aberrations associated with normal phenotypes or clinical abnormalities. Methods: This was a retrospective analysis of seven pedigrees that carried 21q21.1–q21.2 aberrations. G-banding and single-nucleotide polymorphism array techniques were used to analyze chromosomal karyotypes and copy number variations in the fetuses and their family members. Results: All fetuses and their family members showed normal karyotypes in seven pedigrees. Here, it was revealed that six fetuses carried maternally inherited 21q21.1–q21.2 duplications, ranging from 1 to 2.7 Mb, but none of the mothers had an abnormal phenotype. In one fetus, an 8.7 Mb deletion of 21q21.1–q21.2 was found. An analysis of the pedigree showed that the deletion was also observed in the mother, brother, and maternal grandmother, but no abnormal phenotypes were found. Conclusion: This study identified 21q21.1–q21.2 aberrations in Chinese pedigrees. The carriers of 21q21.1–q21.2 duplications had no clinical consequences based on their phenotypes, and the 21q21.1–q21.2 deletion was transmitted through three generations of normal individuals. This provides benign clinical evidence for pathogenic assessment of 21q21.1–q21.2 duplication and deletion, which was considered a variant of uncertain significance and a likely pathogenic variant in previous reports.